Emisiones de dióxido de carbono en estratos de mangle en la Amazonia Oriental Brasileña - Castellón Rodríguez, Nelson (Universidad de Costa Rica, 2020)
Introduction: Carbon dioxide emissions from mangrove soils have a potential impact on the global carbon balance. They are related to anthropic actions and natural processes with interspecific interactions involving physical-chemical and environmental variables. Objective: In this research, the seasonality of carbon dioxide emissions related to different strata of mangrove vegetation, soil physical-chemical makeup and physical environmental factors were evaluated. Methods: Nine plots of 20 x 20 m were demarcated (three for each of the three vegetation strata) in the Experimental Site of the Federal Rural University of the Amazon and the Federal University of Pará in Cuiarana, Salinópolis, Pará, Brazil.  Duplicate soil samples were taken from each plot during three consecutive seasonal periods and analyzed in the laboratory. Carbon dioxide emissions were monitored for 88 days through the basal breathing of the soil methodology; other variables evaluated were soil moisture and temperature, hydrogenic potential, redox potential, carbon and nitrogen of the microbial biomass, organic matter and composition of sand, silt and clay. Precipitation data was obtained from the CMORPH technique of the Climate Forecast Center - NOAA. Information on tides was obtained from the Brazilian Navy’s Fundeadouro de Salinópolis. Results: The results showed that the highest carbon dioxide emissions occurred in the rainy season 2017 on average 7.5 (14.5 TCO2 ha/year) mg/100 cm3. With 10.5 mg/100 cm3 (21 TCO2 ha/year), the adult stratum was the largest source of emissions. The highest seasonal correlations of the emissions in relation to the incubation intervals occurred in the rainy season, in the adult stratum the days 1,2,3,4,3,3 and 5. Using principal component analysis (PCA) it was found that the highest correlations of carbon dioxide emissions and physical-chemical variables occurred in the adult stratum with 56 % variance. The highest correlations were found with the variables soil moisture, Ph, organic matter, carbon and microbial nitrogen. The Kruskal-Wallis test corroborated these results, indicating significant differences between vegetation strata and CO2 emissions (P= 0.0170); and the Tukey test confirmed greater statistical importance of the adult mangrove in relation to the other strata (P= 0.0140). Conclusions: In the three analyzed stations, the highest emissions occurred in the rainy period with an average of 14.5 TCO2 ha/year and the adult stratum was responsible for the highest emissions registering 21 TCO2 ha/year difference that was statistically significant with the other strata (P = 0.0140).